BUSINESS STRATEGY FORMULATION TO ENHANCE THE COMPETITIVENESS OF A BUILDING MATERIALS RETAIL BUSINESS: A CASE STUDY OF TB KARYA MANDIRI JAYA - Hikmal Aryo Seto; Cindy Cornella Sutarli; Naya Lutfiyah Anas; Meta Ulandari; Saddam Dewangga Sofyan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2025)
The rapid development of the construction sector has increased the demand for building materials, creating opportunities as well as intense competition among retail businesses in this industry. Therefore, companies need to develop appropriate strategies to maintain their competitiveness and sustain business growth. This study aims to formulate an effective business development strategy for TB Karya Mandiri Jaya as a building materials retail business. Methodologically, this research employs a single-case qualitative study design, applying strategic management analysis tools, including Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), SWOT Matrix, TOWS Matrix, and Quantitative Strategic Planning Matrix (QSPM). The results of the analysis show that the company has relatively strong internal capabilities with an IFE score of 2.72 and a moderate response to external conditions with an EFE score of 2.36. The SWOT and TOWS analyses indicate several strategic alternatives that can be implemented to enhance competitiveness. Furthermore, the QSPM analysis identifies the most attractive strategy as the implementation of digitalization and the strengthening of internal management systems in order to expand market reach and improve operational efficiency. Unlike prior studies that predominantly rely on descriptive and subjective evaluations for small enterprises, this study contributes theoretically and practically by demonstrating how traditional physical and relational assets must be coupled with dynamic digital capabilities and quantitative strategy prioritization to achieve sustainable competitiveness.